Correlation of Chronic Viral hepatitis B and liver function Tests - Rana Mohsen; Estabraq gayadh; Raghad H. Al-azzawi; Ali Adhiah (مجلة جامعة الانبار للعلوم الصرفة, 2022)
Hepatitis B virus (HBV) infection is one of the important challenges facing the world. The persistence or clearance of HBV is often determined by the host's immune responses. The current study was conducted during June-October 2018 on 80 patients with chronic HBV infection and 96 age- and gender-matched healthy controls. The results showed that most of the patients were males (62.5%) while females constituted 37.5%. The patients' serum was positive for anti-HBc IgG and HbsAG antibodies, while it was negative for anti-Hbc IgM antibodies. These findings were consistent with the interpretation of chronic HBV infection. Four liver function tests were performed, including alkaline phosphatase (ALP), alanine aminotransferase (ALT), aspartate aminotransferase (AST) and total serum bilirubin (TSB). A significant increase in ALP, ALT, and AST levels was observed in HBV patients compared to healthy controls, while TSB showed no significant differences. However, in the receiver operating characteristic curve analysis, only ALP and AST occupied an excellent area under the curve, which was > 0.90.